determine the impact of ethical leadership on organizational learning through the role of innovative organizational mediator in Islamic Azad University - abolfazl samadian (Allameh Tabataba'i University Press, 2018)
the purpose of the present study was to determine the impact of ethical leadership on organizational learning through the role of innovative organizational mediator in Islamic Azad University. The statistical population includes all the employees of the Central Organization of Islamic Azad University, 1535 persons who were selected by using Morgan table and stratified random sampling method. In order to collect data, three standard questionnaires of ethical leadership of Brown et al. (2005), Nifeh organizational learning (2001), and Siegel \u0026 Kaimer (1978) innovative organizational climate were used. After collecting the questionnaires, data were analyzed by means of mean, standard deviation, percentage, frequency and tables through SPSS V22 software and statistical inference of data through structural equation modeling using LISREL software in two part measurement model. And the structural part was doneIn the first part, the technical characteristics of the questionnaire including reliability, convergent validity and divergent validity were investigated. In the second part, path coefficients and significant coefficients were used to investigate the research hypotheses. The results showed that due to the role of innovative organizational mediator, ethical leadership and its components have a positive and significant effect on organizational learning of central organization employees. Ethical leadership influences organizational learning; Ethical leadership affects innovative organizational climate; Organizational learning affects innovative organizational climate.